Implementasi Media Piring Cakra dalam Meningkatkan Pembelajaran Huruf Hijaiyah Anak Usia Dini - Ayi Teiri Nurtiani; Irda Yosa (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2021)
Learning hijaiyah letters is certainly very good if it is learned andtaught to children from an early age, of course by using concrete and interesting mediaaccording to their stage of development so that learning activities are able to present apleasant experience for them. This study aims to describe implementation of the cakraplate media in improving the learning of hijaiyah letters in early childhood. Theformulation of the problem is how implementation of the cakra plate media inimproving the learning of hijaiyah letters in early childhood?. This study uses aclassroom action research (CAR) method using an instrument of early childhood activityobservation sheets. The result showed that in pre-cycle the average value of children inBSB category was 25%, the firs cycle the average value of children in BSB category was36.25%, and the second cycle the average value of children in BSB category was 76.25%.The results of the study showed an increase in hijaiyah learning through the cakra platemedia with an average result that increases in BSB category in early childhood. Thus, theimplementation of the cakra plate media in improving the learning of hijaiyah letters isvery effective and works very well to be applied to early childhood.